The role of employee commitment and employee communication towards successful strategy implementation in Klang valley - Chin, Kah How; Tan, Kiat Hau (2019)
This research focuses on the attempt to investigate employee commitment and employee communication towards successful strategy implementation. The purpose of conducting this research is to examine the relationship between employee commitment and employee communication towards successful strategy implementation. The data for this study was collected using survey questionnaire. For this research, the targeted population is employee who work in Klang Valley. A sample size of 173 sets of questionnaires was distributed to employee in Kuala Lumpur Sentral (KL Sentral). Moreover, the Statistical Package for Social Sciences (SPSS) is being used to analyse the data collected throughout the survey. In addition, regression analysis revealed that “Employee Communication” was significantly predicted towards successful strategy implementation, and followed by “Employee Commitment”. The findings suggested that organization should ensure that communication flow are smooth among all level of management. Besides, organization should recognize the importance of employee commitment and put more efforts in increasing the commitment of employee towards the organization in order to increase organizational success in the long run. Practical contributions are discussed, with future research suggested.